Hubungan Antara Kualitas Kehidupan Kerja Dengan Kepuasan Kerja Karyawan di PT. Nusanet Medan - Irzham Aulya Karnaen; Hairul Anwar Dalimunthe (Universitas Medan Area, 2022)
This study aims to determine and analyze the relationship between the quality of work life and job satisfaction of employees at Nusanet. The sample to be used in this study amounted to 68 employees of Nusanet Medan. Data collection was carried out using a Likert scale model through two variables, namely quality of work life and job satisfaction. Data analysis using product moment correlation technique. The results of this study indicate that the quality of work life has a significant positive relationship with the job satisfaction of the employees of Nusanet Medan. The results of the linearity test with the acquisition of a different F of 10,726 with a different P value of 0.002 0.05 and the results of the correlation analysis of R product moment with the acquisition of an Rxy coefficient value of 0.367 and a P of 0.002 0.01 which also indicates that the higher the quality of work life obtained, the job satisfaction will also be higher. The quality of work life has a contribution to job satisfaction of 13.5% which is indicated by the value of the determinant coefficient (R2) of 0.135. The quality of work life and job satisfaction of Nusanet Medan employees is currently still low.